Kajian Pengaruh Perubahan Putaran Fan terhadap Pembuangan Panas pada Precooling Condenser - Susilawati Susilawati; Tito Riyanto (Retii, 2018)
The heating process plays a role in increasing the dry air temperature (TDB) without any change in the water in the air. This process occurs because air passes through a heating coil or heater. Fan is used to flow air through the heating coil, the goal is to accelerate the process of heat transfer between air and heating coil. Recooling condenser is used to remove some of the heat into the environment in a mechanical dehumidification system. At 0% fan rotation dry air temperature (TDB) entering and exiting the cooling condenser is 26.9 ° C, 72% RH, while at 100% the fan rotation of the dry air temperature (TDB) enters and exits precooling condenser each rated 28.3 ° C, 66% RH and 28.3 ° C, 49%. The sensible heat absorption capacity of the outgoing air precooling condenser increases to 1.75 times greater than the input air